Analisis Perbandingan Penghimpunan Dan Penyaluran Dana Zakat Antara Laz Izi, Laz Dt Peduli, dan Laz Rumah Yatim di Provinsi Riau - Annisa Mahfuzoh (Jurnal Ilmiah Wahana Pendidikan, 2026)
Riau Province, with a predominantly Muslim population, has a zakat potential of IDR 1.8 trillion per year, but the realization of zakat collection is still very low compared to its potential. This study aims to analyze the differences in the performance of zakat collection and distribution between the National Zakat Institution (LAZNAS) Indonesian Zakat Initiative (IZI), LAZ Daarut Tauhid (DT) Peduli, and LAZ Rumah Yatim in Riau Province, and to compare the certification levels of zakat collectors in these three institutions. The study uses a quantitative approach with quarterly data for the 2022–2024 period analyzed using descriptive statistics, the Kruskal-Wallis test, and the Mann-Whitney test. The results show a statistically significant difference in the performance of zakat collection and distribution. LAZ IZI ranks highest in both aspects, followed by LAZ DT Peduli, and then LAZ Rumah Yatim. LAZ IZI also has the highest ratio of amil certification (40%), while LAZ DT Peduli has 25%, and LAZ Rumah Yatim has 0%. LAZ IZI's superiority is supported by a diversified collection strategy, a broad donor base, a varied distribution program, and better quantity and quality of human resources (amil). These findings recommend the need for increased strategic innovation, program diversification, and strengthening of human resource capacity for LAZ DT Peduli and LAZ Rumah Yatim to optimize zakat potential in Riau Province.